Traits plasticity of Sodom Apple (Calotropis procera) along the environmental gradient in the semi-arid environment - Siraj,; Khan, Nasrullah; Okla, Mohammad; Al-amri, Saud; Al-Qahtani, Wahidah; Abdel-Maksoud, Mostafa; AbdElgawad, Hamada (Frontiers in Plant Science, 2023)
Biomass and morphological characteristics of plant species can provide essential insight into how well a species adapts to its environment. The study aims to evaluate how environmental variables (viz., altitude, slope, aspect degree, and soil properties) influence the morphological traits and biomass variability of C. procera in a semi-arid environment. C. procera sample locations were divided into 39 permanent quadrates (5×5 = 25 m2). Slope, aspect degree, slope aspect, altitude, and soil variables (soil moisture, organic matter, nitrogen (N %), and phosphorus (P) gradients were used to quantify morphological parameters (height, diameters, canopy area, volume, and leave/branch biomass) and aboveground biomass. Environmental variables, i.e., altitude and aspect degree, were the most important factor influencing the biomass variation. Altitude and aspect degree are the primary factors affecting soil moisture content; however, they did not directly affect the total biomass of the species. The results also reveal significant plasticity in morphological traits exists concerning elevation and aspect degree. Plant volume was a better indicator of species' total biomass indicated by the regression model. The study also reveals that soil properties such as soil moisture and P dynamics have an important role in enhancing the productivity of the studied plant species. These differences resulted in increased species' tolerance to variable climatic variables and may be utilized to conserve and protect this plant species.